Renoprotective Effects of Hydroxychloroquine and Folinic Acid via ET-1 and NLRP3 Modulation in Reducing Tubular Injury in A Rabbit Model of Methanol-induced Acute Kidney Injury - Prayuda Prayuda; I Gde Raka Widiana; Ketut Suega; Yenny Kandarini; Ni Wayan Winarti; Bambang Purwanto (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Methanol intoxication is associated with significant morbidity and mortality, particularly when acute kidney injury (AKI) developed. Emerging evidence implicates Endothelin-1 (ET-1) and Nucleotide-binding domain leucine-rich repeat-containing pyrin receptor 3 (NLRP3) inflammasome in renal injury, but their roles in methanol-induced AKI remain unclear. To date, no studies have examined whether hydroxychloroquine or folinic acid, which are known to modulate ET-1 and NLRP3 signaling, could mitigate renal injury in this setting. This study evaluated their therapeutic effects in a rabbit model of methanol-induced AKI.METHODS: The animals subjects were randomly assigned to four groups: control group receiving aquabidest, folinic acid group receiving 2 mg/kg body weight (BW) intraperitoneal folinic acid, hydroxychloroquine group receiving 30 mg/kg BW oral hydroxychloroquine phosphate, and combination group receiving both folinic acid and hydroxychloroquine at the same dosages. Histopathological evaluation of tubular injury scores and immunohistochemical analysis of ET-1 and NLRP3 expression were then conducted.RESULTS: Expressions of ET-1, NLRP3, and tubular injury scores were significantly lower in the hydroxychloroquine, folinic acid, and combination therapy groups compared to the control group (p<0.001). Expression of ET-1 was lowest in folinic acid group (59.38±0.71%), followed by combination group (62.23±1.98%) and hydroxychloroquine group (62.43±1.81%), compared to control group (72.14±1.02%). Expression of NLRP3 was lowest in combination group (58.94±1.05%), followed by folinic acid and hydroxychloroquine group, which showed equal values (60.57±1.38%), compared to control group (72.15±1.02%). Tubular injury scores were also lowest in combination group (27.07±3.16%), followed by hydroxychloroquine group (45.29±1.75%) and folinic acid group (48.38±2.49%), compared to control group (77.15±1.66%).CONCLUSION: Expression of ET-1 and NLRP3, as well as tubular injury scores, are significantly lower in all treatment groups compared to control, suggesting hydroxychloroquine and folinic acid demonstrated renoprotective effects in methanol-induced AKI, likely through modulation of ET-1 and NLRP3 pathways.KEYWORDS: methanol intoxication, acute kidney injury, hydroxychloroquine, folinic acid, endothelin-1, NLRP3 inflammasome, experimental animal models, rabbits